Plant Growth and Antioxidant Resistance of Soybean Genotypes as Influenced by Silicon Nanoparticles, Calcium, and Aluminum Rates - Hossein Mozafari; Mohammad Mohsen Salajegheh; Hassan Salari; Hakimeh Oloumi; Seyed Mozaffar Mansouri (International Journal of Agronomy)
Metal nanoparticles show various physiological effects on stressed plants. Silicon oxide nanoparticles may promote plant growth and antioxidant resistance, while copper oxide nanoparticles can worsen stress and are less effective in improving plant resistance. However, little is known about the effects of the Al3+ in soybean plants. This study investigated the effect of silicon nanoparticles and calcium ions on the response of soybean genotypes to oxidative stress under excess aluminum. Interaction and combined effect of silicon nanoparticles 5 mg/L with a diameter of 15 nm and Ca2+ ions 1 mM on further improvement of growth and reduction of oxidative stress in soybean oil seeds of the William cultivar under Al3+ stress in hydroponic culture media. For this purpose, antioxidant and physiological responses and growth and biochemical changes of soybean plants under experimental treatments containing Al stress, nanoparticles, and calcium were investigated in a standard greenhouse environment. The results showed that the application of silicon nanoparticles combined with calcium influenced growth parameters (leaf surface and leaf pigments) and total protein due to reduced oxidative stress caused by Al3+ toxicity on William’s soybean plant. In addition to silicon nanoparticles and Ca2+ to the medium containing Al3+ stress, the correlation between the plasma membrane and reduction of Al3+ absorption was obtained. The findings suggest that the William cultivar exhibits a good response to nanoparticles and Ca2+ under Al3+ stress.